Recently discovered neo-assyrian royal inscriptions from the review palace and negral gate of Nineveh - Al-Juboori, Ali. Y. (Iraq, 2017)
Between 1987 and 1992, Iraqi archaeologists under the direction of the local Inspectorate of Antiquities undertook excavations at Nineveh. In particular, they excavated east of the mosque located on the smaller mound of Nebi Yunus and at the Nergal Gate, the middle gate of the northern city wall. At the Nergal Gate, an inscription of Sennacherib was found on two bull colossi and two paving stones. At Nebi Yunus, a few inscribed clay and stone objects were discovered in the ruins of the armoury, the so-called “Rear Palace” (or “Review Palace”). These included a slab of Ashurnaṣirpal II, a prism fragment of Esarhaddon, two human-headed winged bull colossi of Esarhaddon, a winged-bull of Ashurbanipal, and an unsculpted wall slab of Ashurbanipal. Then, after east Mosul was liberated from ISIS/Daʾesh occupation in early 2017, seven further inscriptions of Esarhaddon were discovered in looters’ tunnels under the destroyed mosque. All of those inscriptions are edited here.